CUSTOMER ENGAGEMENT AND BUILDING BRAND LOYALTY ON THE SOCIAL MEDIA-BASED COMMUNITY ON FACEBOOK AND INSTAGRAM IN INDIA - Jain, Aditi (2020)
Building and maintaining brand loyalty through customer engagement is one of the central research areas for authors and to expand and explore other areas marketers are trying out and utilizing social media, keeping up with the digital era. With significant growth in the usage of social networking platforms around the world, this research aims to explore and determine the effect of customer engagement and interaction on building brand loyalty by focusing on the drivers of loyalty on the communities of social networking platforms. To find out and help marketers build brand loyalty, this study will find out ways to gain customer's trust and reliability for the long term association. Data is collected by circulating surveys to participants and is analyzed through IBM SPSS software. The results from the analysis prove the hypothesis developed and represent a positive relationship between the different variables and suggests that through regular and continuous engagement on communities, marketers can enhance customer's trust, awareness, and satisfaction which ultimately leads towards the path of loyalty. Moreover, customers show progressive responses to the information presented on social communities and are increasingly showing interest in participation and interaction thus influencing their behavior towards building an association with a brand. The study opens up with the limitations and recommendations for further studies towards the end.